(untitled) (مجلة العلوم الإنسانية والتطبيقية, 2016)
In many cities today, own car has become an important and dominant mode of transport. Increasing dominance of own car as a mode of transport is due to its inherent advantages associated with its usage. In Tripoli, Libya due to rapid increase in car usage associated with poor public transport system has resulted in increase of traffic congestion, accidents and lack of parking spaces. This study aims to identify the factors preventing own car from shifting to public transport system (PT) and to develop model shift from own car to public transport in order to formulate policies to achieve this. A policy to enhance public transport system usage and control car ownership simultaneously has become necessary for solving traffic congestion problems. A questionnaire survey was carried out on users of transport in Tripoli such as own car, taxis, microbuses and coaches drivers (n = 900). The probability of car drivers shifting to public transport was examined based on scenario several options such as reduction in public transport travel time and travel cost. Reduction in total travel time and cost for public transport mode emerged as the most important elements in attracting car users towards using public transport system. Logistic regression technique has been used to analyze the factors that impact users to switch their trips to public transportation alternatives. Statistical Package for Social Science (SPSS) version 19 and Excel 2007 software were used to analyze the questionnaire in this study.